Force-feeding and the legacy of torture in the 'war on terror'. Issue 7 (9th August 2019) - Barnes, Jamal
ABSTRACT: In 2013, a mass hunger strike took place in Guantanamo Bay as a response to the indefinite detention and unjust treatment of prisoners captured during the 'war on terror'. In response, the US used force-feeding against the hunger strikers, arguing it was needed to save their lives and uphold US security. Although the US argued its force-feeding policy was legal and humane, human rights and medical organisations criticised US force-feeding practices as constituting torture or cruel, inhuman or degrading treatment or punishment. This article argues that the US undermined international human rights norms, laws and medical ethics in its management of hunger striking prisoners by using force-feeding to suppress hunger strikers and achieve national security interests. In doing so, the Obama administration reignited accusations of US torture and harmed its ethical standing in international society. The article argues that the US needs to incorporate international human rights standards into its hunger striker policy to uphold the dignity of prisoners in detention and overcome its legacy of torture in the 'war on terror'.